2018
DOI: 10.1177/109258721802300104
|View full text |Cite
|
Sign up to set email alerts
|

Can interpretive graphics influence visitor behavior in an exhibit space?

Abstract: Exhibit signage and graphics projects are most successful when they involve collaborative planning and formative evaluation throughout the process. Lincoln Park Zoo set out to combine interpretive best practices and visitor evaluation methods for the newly renovated eastern black rhinoceros yard in 2010. Evaluation methods included prototyping, visitor tracking, and informal interviews. After installation of the new graphics, visitor time spent looking at both the signs and the exhibit increased. Results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Hall et al (2010) found that visitors related more positively to communications on signs with narrative structures and emotional content than other forms of messaging. Price et al (2018) found that hands-on elements increased visitor engagement time with exhibits. Benton and Sinha (2011) found that visitors favored dioramas, maps, models, and vivid visual images of tigers over text in an exhibit space in India.…”
Section: Interpretive Techniquesmentioning
confidence: 98%
See 1 more Smart Citation
“…Hall et al (2010) found that visitors related more positively to communications on signs with narrative structures and emotional content than other forms of messaging. Price et al (2018) found that hands-on elements increased visitor engagement time with exhibits. Benton and Sinha (2011) found that visitors favored dioramas, maps, models, and vivid visual images of tigers over text in an exhibit space in India.…”
Section: Interpretive Techniquesmentioning
confidence: 98%
“…The results of this effort appear in a series of four articles published as a special issue in the Journal (2013-18(2)). Their study provided empirical Barrett et al (2017), Beck et al (2015), Benton andSinha (2011), Bixler et al (2015), Bourque et al (2014), Britt (2017), Burris (2019), Douglas et al (2018), Gilson and Kool (2019), Hall et al (2010), Ham (2013), Henker and Brown (2011), Knapp and Forist (2014), Lawhon et al (2017), Macklin et al (2010), Montero et al (2018), Morgan and Hwang (2014), Moss et al (2010), Ogle (2016), Stern (2013a, 2013b), Price et al (2018), Rahaman and Kian (2017), Reese (2013), Ren and Folta (2016),…”
Section: Interpretive Techniquesmentioning
confidence: 99%
“…Natural area visitors most frequently receive information through static content like pamphlets and signs (Guo et al 2015 ). While such static information can improve participant knowledge levels (Guo et al 2017 ; Sharp et al 2012 ; Young and Witter 1994 ), their persuasive influence varies (Guo et al 2017 ; Price et al 2018 ). The potential to influence attitudes and behaviors requires effective message design and presentation (Young and Witter 1994 ) that incorporates personal relevance and results in greater message elaboration (Petty and Cacioppo 1986 ).…”
Section: Introductionmentioning
confidence: 99%